Essays on the causes and consequences of international migration - Elsner, Benjamin (Trinity College (Dublin, Ireland). Department of Economics, 2012)
This thesis is a collection of three essays on the economic consequences of international migration. The first chapter studies the impact of emigration on wages in the sending countries. It exploits a change in the migration laws in Europe following EU enlargement in 2004 which triggered an emigration wave of 1.2 million workers within 3 years. Using data from Lithuania, the UK and Ireland, I find that emigration led to an increase in the wages of stayers. For a 10 percentage-point increase in the emigration rate, wages increased on average by 6.6%. This effect is statistically significant for men, but not for women.
Keywords: Economics, Ph.D.; Ph.D. Trinity College Dublin